Hydrogels: Paramagnetic Levitational Assembly of Hydrogels (Adv. Mater. 8/2013). (15th February 2013) - Tasoglu, Savas; Kavaz, Doga; Gurkan, Umut Atakan; Guven, Sinan; Chen, Pu; Zheng, Reila; Demirci, Utkan
<x xml:space="preserve">Abstract</x> Manipulation and assembly of cell‐encapsulating hydrogels offer unique opportunities for regenerative medicine, microphysiological system engineering, pharmaceutical research, biological research, and space sciences. Utkan Demirci and co‐workers show on page 1137 that temporal and spatial control over hydrogels in microscale can be exerted by exploiting their paramagnetic properties without using magnetic nanoparticles. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>